Enseignement de l’intonation et neurolinguistique - Philippe Martin (Corela, 2020)
As emphasized by Élisabeth Guimbretière (1994) and Bernard Dufeu (2008), the teaching of pronunciation, and in particular intonation, remains a neglected part of learning French as a foreign language. While FSL textbooks sometimes devote a few chapters to the pronunciation of syllables and words, intonation takes, at best, only a few paragraphs, describing the traditional functions of intonation indicating the declarative or interrogative modality of the sentence, and their variants. In fact, linguistic description, still based on written text syntax, does not do much better and fails to clearly determine the role, however essential, of intonation in understanding speech. The current dominance of the autosegmental-metrical approach, mixing the phonetic and phonological aspects of intonation, does not help to clarify the issue.However, recent discoveries concerning the correlation between stress groups stressed syllables and brain waves, and in particular delta (varying from 0.8 to 4 Hz), theta (from 4 to 10 Hz) and gamma (from 30 to 80 Hz) accounts not only for the rhythmic variations of stress groups in French, but also allows to better understand the reasons to have a prosodic structure specific to every language. The fact that the prosodic structure pre-exists syntax and lexical selection both in production and perception, in spontaneous and read speech, justifies the imperative need to teach the prosodic system of the language in question before lexicon and syntax.